Comparison of biomass production of Pennisetum purpureum clones N fertilized - Crespo, Gustavo; Álvarez, J. (Cuban Journal of Agricultural Science, 2016)
In a random block design with four replications, was compared the biomass production of seven Pennisetum purpureum clones obtained by tissue culture (CT 21, CT 14, CT 36, CT 30, CT 115, CT 43 and CT 18) and fertilized with 60 kg/ha/cut of N (as urea). Three cuttings were practiced with 120 d of regrowth each. In the poor rainy months 30 mm of water was applied by aspersion. In each cutting fresh matter (FM) and DM yields, height and number of tillers/clump were determined. At the end of the experiment population of clumps were established. Clone 21 surpassed the rest in FM (142.2 g/ha) and DM (45.7 t/ha) yields, although in this latter case differences were not significant regarding clones 18, 36, 14 and 30. In the three cuttings carried out, clone 21 showed higher height (188 to 198 cm). In the third, clone 21 showed greater tiller values per clumps (> 17.6), but without differing significantly from clones 18, 36, 14 and 30. The lowest population value at the end of the experiment was shown by CT-115 (1.36 clumpss/m), without significant differences regarding the rest. Results cannot deny the variability between clones and allow recommending clone 21 for forage production. Key words: Pennisetum purpureum cv. king grass, somaclones, performance